Strengthening Exclusive Breastfeeding Through the ErDa Model: A Community-Based Support and Monitoring Initiative - Irmawati (Poltekkes Kemenkes Semarang, 2026)
Exclusive breastfeeding is vital for infant health, yet record-keeping and reporting at primary health centers in Semarang remain suboptimal. A preliminary study at Puskesmas Tlogosari Kulon revealed the absence of a dedicated cohort register for breastfeeding mothers, resulting in inaccurate and inconsistent data. Accurate data, however, is essential to inform policy and decision-making. This community service program aimed to establish and train the DAKASI (Dasa Wisma Kawal ASI Eksklusif) team as companions for breastfeeding mothers while implementing exclusive breastfeeding record-keeping practices. The program followed five stages (5P): preparation, member recruitment, training, mentoring and practice in exclusive breastfeeding record-keeping using a cohort register, and program strengthening. Results showed the formation of a 15-member DAKASI team, improved knowledge (mean score increased from 60.61 pre-test to 82.84 post-test), and improved practical skills in record-keeping (from 63.34 to 87.21). The training effectively enhanced both cognitive and practical abilities of DAKASI cadres. In conclusion, DAKASI successfully provided mentoring and exclusive breastfeeding documentation at the community level while also delivering education and motivation to mothers.